HUBUNGAN MOTIVASI BELAJAR DAN MINAT BELAJAR TERHADAP KEMANDIRIAN BELAJAR - yono, nur seti (Borobudur Counseling Review, 2022)
This study aims to examine the relationship between learning motivation and interest in learning with learning independence in class 6D SDIT Ihsanul Fikri, Magelang City. This study uses a correlational type of research, the reason being to find out the correlation between learning motivation and interest in learning to the independence of learning in class 6D SDIT Ihsanul Fikri, Magelang City, totaling 30 students. The results showed that the X1 coefficient value of 0.389 can be interpreted that if learning motivation (X1) increases by one point, learning independence (Y) increases by 0.389 points with the assumption that other variables remain. While the X2 coefficient of 0.783 can be interpreted that if interest in learning (X2) increases by one point, then learning independence (Y) increases by 0.783 points with the assumption that other variables remain. The results of this study also show that the coefficient of determination obtained is 0.761 and fcount is greater than ftable at a significance level of 5%, which is 49,965 3.32, which means that together there is a positive relationship between the variables of Learning Motivation and the variable of Learning Interest on the variable of Learning Independence. In this study it is proven that learning motivation and interest in learning are related to learning independence. The higher students' learning motivation and interest in learning will make these students more independent in learning. Keywords: Learning Motivation, Learning Interest, Learning Independence.